No evidence for induction of ABC transporters in peripheral blood mononuclear cells in humans after 14 days of efavirenz treatment - Burhenne, Jürgen; Matthée, Anne-Kathrin; Pasáková, Ivana; Röder, Claudia Stephanie; Heinrich, Tilman; Haefeli, Walter E.; Mikus, Gerd; Weiß, Johanna (Antimicrobial agents and chemotherapy, 2010)
Intracellular concentrations of antiretroviral drugs in peripheral blood mononuclear cells (PBMCs) are an important determinant of therapeutic success. In vitro data indicate that efavirenz induces several ATP-binding cassette (ABC) transporters, and pharmacogenetic studies found an association between ABCB1(C3435T) and efavirenz exposure and between this polymorphism and improved virological outcomes. We therefore aimed to clarify whether efavirenz also induces ABC transporters in vivo in PBMCs and whether intracellular concentrations might be altered after induction. Twelve healthy individuals received multiple oral doses of efavirenz over 14 days (400 mg once daily). Blood samples were drawn on study days 1 (single dose) and 14 (multiple dose), and efavirenz concentrations were analyzed by liquid chromatography-tandem mass spectrometry. Expression of P glycoprotein (P-gp) and of the multidrug resistance-associated proteins 1 and 2 as well as P-gp activity was analyzed in PBMCs on day 1 and day 14 using real-time reverse transcription-PCR (RT-PCR) and rhodamine 123 efflux. Although a clear autoinduction could be confirmed by a significant decrease of efavirenz exposure from day 1 to day 14, efavirenz did not change expression of the ABC transporters or P-gp activity in PBMCs. Moreover, intracellular concentrations of efavirenz were 1.3- to 1.8-fold higher than the corresponding plasma concentrations, and the intracellular/plasma concentration ratio remained constant during the treatment and did not correlate with ABC transporter expression or function. In conclusion, our study confirmed that intracellular concentrations of efavirenz are independent from these efflux transporters and demonstrated for the first time that the transporters are not induced in PBMCs in vivo after 2 weeks of treatment with efavirenz.
Gesehen am 22.03.2023